Multilinguisme et injustice sociale linguistique au Botswana - Kagiso Jacob Sello (OpenEdition, 2019)
Botswana adheres to the idea of multilingualism. However, nothing is being done to give effect to this recognition. Only English and Setswana are used for the provision of public services by the government. As such, members of linguistic minorities are victims of language related social injustice. This article will propose some directions for reflection.